Introduction to Field-Being Philosophy : An Anthology of Lik Kuen Tong's Thought - Dykeman, Therese Boos; Weed, Laura E. (Cambridge Scholars Publishing, 2022)
This text is the first concise anthology of Lik Kuen Tong's Field-Being philosophy. In addressing the ontology of both Eastern and Western thought, Field-Being philosophy offers a new metaphysics. Inclusively, it makes room at the table of philosophy for indigenous philosophy, and, foundationally, it rethinks the universe and the global world ontologically as ""activity"" and ""relationality."" A comprehensive philosophy, it considers what is as movement, as well as the what of movement, and inventively adds the concept of ""betweenness."" This philosophy of movement or ""activity,"" being fut.
Keywords: Tang, Liquan, -- 1935-; Philosophy, Chinese.; Philosophie chinoise.; Philosophy, Chinese